1992
DOI: 10.1021/ac00031a015
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic order as a function of surface coverage in alkyl-modified silicas: spin probe studies

Abstract: The chemically modified surface plays an Important role In retention In reversed-phase liquid chromatography. One surface factor that might affect retention Is solute expulsion due to partial ordering of the grafted chains at sufficiently high grafting densities. This study has shown by the use of the electron paramagnetic resonance technique of spin probing that spectroscopic evidence exists for an Increase In molecular order of the bonded octadecyl phase as a function of grafting density. The spin probe, DOX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…EPR studies using two different spin probes found that the rotational mobilities of the probes decreased with increasing surface coverage . This study, along with others, has postulated the existence of at least two types of regions in the interphase due to aggregation or ordering of the alkyl chains. This effect is especially pronounced against a nonwetting solvent such as water, where the chains have been shown to collapse nearly into the plane of the substrate …”
mentioning
confidence: 64%
“…EPR studies using two different spin probes found that the rotational mobilities of the probes decreased with increasing surface coverage . This study, along with others, has postulated the existence of at least two types of regions in the interphase due to aggregation or ordering of the alkyl chains. This effect is especially pronounced against a nonwetting solvent such as water, where the chains have been shown to collapse nearly into the plane of the substrate …”
mentioning
confidence: 64%
“…At high bonding density, the molecules become crowded, less mobile, and more disordered and project a rigid and rough surface to probe fluids. Decreases in mobility of attached molecules ("freezing") with increased bonding density have been observed by solid-state NMR, 58,59 ESR, 60 fluorescence, 61 and molecular dynamics. 62 The literature offers additional support to our conjecture concerning molecular roughness and rigidity.…”
Section: Resultsmentioning
confidence: 96%
“…At high bonding density, the molecules become crowded, less mobile, and more disordered and project a rigid and rough surface to probe fluids. Decreases in mobility of attached molecules (“freezing”) with increased bonding density have been observed by solid-state NMR, , ESR, fluorescence, and molecular dynamics 3 Contact angle hysteresis for water (·), CH 2 I (▪), and C 16 H 34 (▴) on silicon wafers treated with Me 3 SiNMe 2 for various durations. …”
Section: Resultsmentioning
confidence: 99%
“… where 〈cos 2 (θ)〉 is the mean angular fluctuation of the θ angle between the direction of the z main magnetic axis and the D // direction. Under the approximation of an axial symmetry for the nitrogen hf tensor, S can be estimated from the measurable EPR parameters through the Eqn (6)27, 28 where the A' // and A' ⟂ are the apparent N hf tensors submitted to motional averaging, and A zz , A xx , A yy are the real principal values determined by computer simulation of the rigid limit spectrum.…”
Section: Resultsmentioning
confidence: 99%